2021
DOI: 10.3389/fncir.2021.693073
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Electrical Stimulation Ameliorates Traumatic Brain Injury-Induced Sensorimotor and Cognitive Deficits in Rats

Abstract: Objective: Individuals with different severities of traumatic brain injury (TBI) often suffer long-lasting motor, sensory, neurological, or cognitive disturbances. To date, no neuromodulation-based therapies have been used to manage the functional deficits associated with TBI. Cortical electrical stimulation (CES) has been increasingly developed for modulating brain plasticity and is considered to have therapeutic potential in TBI. However, the therapeutic value of such a technique for TBI is still unclear. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Several preclinical studies have demonstrated the therapeutic potential of CES for TBI. Four weeks of CES treatment in TBI rats improved locomotor function and spatial memory recovery [ 14 , 15 ]. Three-week electrical stimulation may enhance angiogenesis and improve the cognitive deficits induced by TBI [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several preclinical studies have demonstrated the therapeutic potential of CES for TBI. Four weeks of CES treatment in TBI rats improved locomotor function and spatial memory recovery [ 14 , 15 ]. Three-week electrical stimulation may enhance angiogenesis and improve the cognitive deficits induced by TBI [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation protocol, such as the different positions of electrodes and neural targets, the current intensity, the duration, the timing of stimulation, the usage of the concomitant task, and the time point of the application of electrical stimulation, may influence the therapeutic outcomes of electrical stimulation. Various stimulation protocols have been tried in animal models and have shown their potential in the treatment of TBI [ 10 , 14 , 15 ]. These studies used 3 to 4 weeks of invasive CES.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the methods mentioned above, there are several other promising electrical stimulation modalities that may be effective in the treatment of TBI sequelae. Electrical cortical stimulation, an invasive method where electrodes are implanted near the cortical surface, can be used to modulate brain plasticity to treat sensorimotor and cognitive deficits in rats [137]. Similarly, epidural electrical stimulation utilizes pulsed stimulation protocols applied to electrodes implanted in the epidural or subdural space to enhance motor recovery and brain activity [138][139][140].…”
Section: Additional Stimulation Methodsmentioning
confidence: 99%
“…The team found both methods to improve rats' performance on Y-maze and single pellet reaching tasks but noted the improvement was greater in animals treated with direct cortical stimulation. 39 More recently, Kuo et al 40 stimulated motor and parietal cortex in 23 post-WDM rats, measuring significant improvement across a number of functional domains including short-term memory, locomotor ability, and sensory function.…”
Section: Invasive Neurostimulation For the Treatment Of Functional De...mentioning
confidence: 99%